2021
DOI: 10.3390/foods10123073
|View full text |Cite
|
Sign up to set email alerts
|

Food Security and the COVID-19 Crisis from a Consumer Buying Behaviour Perspective—The Case of Bangladesh

Abstract: Since COVID-19 was confirmed in Bangladesh in March 2020, the government have enacted stringent measures to prevent the spread of the coronavirus, which has had a significant impact on people’s lives. Food consumption habits of consumers have shifted as a result of declining grocery shopping frequency, negative income shock, and food prices shooting up. This paper aims to explore Bangladeshi consumers’ buying behaviour in association with the stress generated from a food supply shortage during the COVID-19 pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 78 publications
1
31
0
Order By: Relevance
“…Senauer [ 65 ] revealed that many people worldwide are hungry because they do not have sufficient money (poverty) and cannot afford enough food to eat appropriately. Declines in income make consumers more stressed and concerned regarding potential food crises, prices, safety and security, nutrition, and food quality [ 13 ]. There is also a possibility that food security and nutritional value would degrade as income inequality rises [ 42 ].…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Senauer [ 65 ] revealed that many people worldwide are hungry because they do not have sufficient money (poverty) and cannot afford enough food to eat appropriately. Declines in income make consumers more stressed and concerned regarding potential food crises, prices, safety and security, nutrition, and food quality [ 13 ]. There is also a possibility that food security and nutritional value would degrade as income inequality rises [ 42 ].…”
Section: Theoretical Framework and Hypothesismentioning
confidence: 99%
“…Producers might sell adulterated and harmful foods. Consumers were more stressed during COVID-19 since they were not receiving salaries regularly, and many lost their jobs [ 13 ]. Meanwhile, the World Bank [ 14 ] stated that the pandemic caused currency depreciation and global agricultural commodity prices to rise by 40% in 2021 compared to January 2020.…”
Section: Introductionmentioning
confidence: 99%
“…According to Tartib Parate Executive, it is an execution carried out by the holder of the security right (pawn and mortgage) without the assistance or interference of the District Court but only based on the assistance of the State Auction Office (Hidayah, Nasyi'ah, & Jundiani, 2019). Meanwhile, according to Herowati Poesoko, the implementation of the Parent Executive is the easiest and simplest way for creditors to recover their debt when the debtor is in default, compared to execution through assistance or interference by the district court (Rabbi, Oláh, Popp, Máté, & Kovács, 2021). If the borrower is in failure, this signifies, the lender can carry out the execution of the object of guarantee without having to ask for fiat from the Head of the District Court, and therefore the procedure is easier and costs less.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the warehousing invoice system, Conformity Assessment Agency is also known, which means a recognized educational organization that carries out a collection of actions to assess or show that certain requirements concerning items, services, and/or personnel have been met (Rabbi et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As the infection rate was gradually increased, the Government was forced to extend the ongoing strict lockdown to slow down the rapid spread of COVID-19 infection. The government effectively implemented the lockdown by imposing strict travel restrictions, stay-at-home orders, and market/shopping mall closures, leading to a sudden drop in food security among low-income people residents [ 11 ]. Adverse effects on domestic food supply chains, shocks in food production, and income losses are causing mental stress and food insecurity during the strict lockdown.…”
Section: Introductionmentioning
confidence: 99%